Pendampingan Teman Sebaya dan Peran Orangtua dalam Mewujudkan Remaja Bebas Narkoba dan Sehat Reproduksi di Wilayah Pesisir - Fitriani Pramita Gurning; Fauziah Nasution; Eliska Eliska (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
The frequent occurrence of drug abuse and premarital sex which is indicated from the frequent occurrence of raids on drug cases in Langkat District, the high number of early childhood marriages that still occur. This is compounded by the inactivity of religiously oriented adolescent activities, where previously youth groups tended to be active in empowering adolescents. School is one of the places for adolescent interaction and in one day many teenagers spend their time in school. The form of community facilitation activities with counseling activities, peer education training and mentoring through whatup media groups and also conducting counseling to parents aimed at increasing the knowledge and role of parents as agents of socialization to adolescents, peer education training aimed at increasing the role of adolescents as peer educators and assistance aimed at assisting adolescent peer educators in planning for, and dealing with problems related to the dangers of drugs, HIV/AIDS and reproductive health. An increase in students' knowledge after getting counseling and training about the dangers of drugs, HIV/AIDS and adolescent reproductive health. Suggestions for further activities are the need for traning of trainers for adolescent doctors and assistance in making adolescent health programs.